2022
DOI: 10.1089/lrb.2021.0015
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoscintigraphic Investigations for Axillary Web Syndromes

Abstract: Background: Axillary web syndrome (AWS) is a frequent complication after surgery for breast cancer, but its lymphatic involvement is not definitively established. Here we report the results of lymphoscintigraphic investigations in patients with AWS. Methods and Results: We conducted a retrospective, single-center review of lymphoscintigraphic investigations performed in 46 patients with AWS that was either clinically obvious or suspected. Of this group, 23 patients had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Some of these lympho-fluoroscopic figures under these tattoos are similar to what is observed at the level of the upper limb with Axillary Web Syndrome (AWS). 34 These AWS situations are frequent in patients operated for Breast Cancer but have also been reported in non-cancerous situations. 35–37 In the framework of lymphoscintigraphic investigations after subcutaneous injection of radiocolloids, it has been demonstrated that they are secondary to lymph stasis, lymphangitis and lymphangio-obliteration.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Some of these lympho-fluoroscopic figures under these tattoos are similar to what is observed at the level of the upper limb with Axillary Web Syndrome (AWS). 34 These AWS situations are frequent in patients operated for Breast Cancer but have also been reported in non-cancerous situations. 35–37 In the framework of lymphoscintigraphic investigations after subcutaneous injection of radiocolloids, it has been demonstrated that they are secondary to lymph stasis, lymphangitis and lymphangio-obliteration.…”
Section: Discussionmentioning
confidence: 91%
“…35–37 In the framework of lymphoscintigraphic investigations after subcutaneous injection of radiocolloids, it has been demonstrated that they are secondary to lymph stasis, lymphangitis and lymphangio-obliteration. 34 In BC patients with AWS, swelling at the onset of the syndrome is frequently seen. However, with the development of collaterals, clinically obvious edema remained in only one-third of the cases and was not observed in patients who presented no edema as part of their initial symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study in which lymphoscintigraphy was performed in patients with AWS, it was reported that approximately 90% of the patients had changes such as decreased lymphatic function and obstruction of lymphatic vessels and 67% had collateral lymphatic vessels. These results suggest the involvement of lymphatic vessels in the pathogenesis of AWS [6]. In another report, a biopsy of cord-like structures in seven patients with AWS revealed that lymphatic vessels were involved in three cases, of which a thrombus in the lymphatic vessels was noted in one [7].…”
Section: Introductionmentioning
confidence: 80%
“…A consistent hypothesis is that the cord contains one or more tiny lymphatic vessels tethered to each other or the surrounding tissue by extravasated and cross-linked fluid proteins [8,9]. It is also considered a type of Mondor's disease in which subcutaneous cord-like induration appears due to inflammation or obstruction of veins running in the shallow subcutaneous layers of the chest, upper abdomen, and upper extremities [6].…”
Section: Introductionmentioning
confidence: 99%